The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsami.1c22770
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transition-Induced Raman Enhancement in Bioinspired Diphenylalanine Peptide Nanotubes

Abstract: Semiconducting materials are increasingly proposed as alternatives to noble metal nanomaterials to enhance Raman scattering. We demonstrate that bioinspired semiconducting diphenylalanine peptide nanotubes annealed through a reported structural transition can support Raman detection of 10–7 M concentrations for a range of molecules including mononucleotides. The enhancement is attributed to the introduction of electronic states below the conduction band that facilitate charge transfer to the analyte molecule. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…50 Aer cycling, the C-C peak appears at 284.8 eV, 10,51 and the lowest energy peak of 282.4 eV is attributed to environmental contamination. 52 Fig. 5e shows C 1s spectrum of ferrocene/AC cathode before and aer cycling.…”
Section: Resultsmentioning
confidence: 99%
“…50 Aer cycling, the C-C peak appears at 284.8 eV, 10,51 and the lowest energy peak of 282.4 eV is attributed to environmental contamination. 52 Fig. 5e shows C 1s spectrum of ferrocene/AC cathode before and aer cycling.…”
Section: Resultsmentioning
confidence: 99%
“…5C). 167 Apart from small molecular organic semiconductors, a few semiconductive organic substrates, includ-ing π-conjugated polymers 168,169 and peptide nanotubes, 170 are also reported.…”
Section: Semiconductorsmentioning
confidence: 99%
“…The enhancement is attributed to the introduction of electronic states below the conduction band that facilitate charge transfer to the analyte molecule. [ 29 ] Thus, in this study, we have investigated the influence of both temperature and water content on Fmoc‐FF gel formation. We have found that microsphere formation can be tuned by increasing the water content and by heating the solution.…”
Section: Introductionmentioning
confidence: 99%